2020
DOI: 10.5606/ehc.2020.71413
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary approach in the treatment of osteoid osteoma with radiofrequency ablation

Abstract: Osteoid osteoma (OO) is a benign tumor that is frequently seen in young people usually in the second and third decade. Tumor localization may be in cortical or cancellous bone. [1] Radiologically, a surrounding sclerotic lesion and a structure called "nidus" are present. Clinically, night pain is typical and frequently responds well to nonsteroidal drugs. There are many treatment modalities for OO including medical treatment, percutaneous radiofrequency ablation (RFA) treatment, and open surgical procedures. [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 18 publications
0
11
0
1
Order By: Relevance
“…Four intracapsular neck of femur lesions aged below 11 years were excluded from our study due to different diagnoses among the consultants requiring single or multiple biopsy and change of intervention as necessitated. Percutaneous CT guided radiofrequency ablation in cases of typical presentation, with clinical and imaging conclusive of diagnosis, yields better results and patient compliance 9,10 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Four intracapsular neck of femur lesions aged below 11 years were excluded from our study due to different diagnoses among the consultants requiring single or multiple biopsy and change of intervention as necessitated. Percutaneous CT guided radiofrequency ablation in cases of typical presentation, with clinical and imaging conclusive of diagnosis, yields better results and patient compliance 9,10 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the location of the lesion in proximal femur (intra or extracapsular) and its atypical clinical presentation sometimes surprises with tissue diagnosis warranting a biopsy at preprocedural level to establish a working diagnosis 3-6 . However, management of osteoid osteoma by techniques like computed tomography (CT) guided percutaneous radiofrequency ablation or percutaneous bone drilling have yielded promising results [7][8][9][10] .…”
mentioning
confidence: 99%
“…Data reported in the literature have demonstrated that in case of symptomatic recurrence after the first RFA treatment, re-ablation is almost always resolutive with complete disappearance of symptoms, as suggested by the revision of the literature proposed [ 10 , 16 20 , 23 25 , 36 , 39 , 42 44 , 46 , 48 50 28 – 43 , 92 , 44 51 , 54 56 ] (Table 2 ).…”
Section: Radiofrequency Ablation (Rfa)mentioning
confidence: 92%
“…The most commonly used technique for the definitive treatment of OO lesions in recent years is percutaneous CT-guided radiofrequency ablation (RFA). [ 10 , 11 ] However, percutaneous treatment has some limitations. The process lasts for four to six min, the temperature rises up to 90 degrees during this time,[ 12 - 14 ] and hyperthermia in the surrounding tissues may occur.…”
Section: Introductionmentioning
confidence: 99%